Schools Zoning System in the New Student Admission in Indonesia: An Evaluative Study from Equitable Education Management Perspective - Musadad, Akhmad Arif; Purwanta, Hieronymus (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study aims to examine the implementation of the school zoning system from a justice perspective. Through this research, we could understand how far social justice has been obtained during the zoning system's implementation and the future challenges. The research questions are: (1) Why did the government implement a zoning system? (2) How was the zoning system implemented? (3) How did school principals and history teachers respond to changes in student’s academic quality as a result of the application of the zoning system? The research was conducted qualitatively with a case study approach in the former residency area of Surakarta and the Special Province of Yogyakarta to answer the questions. The data was collected through document analysis, interviews, and observation. The results show that implementing the school zoning system in the New Students Admission was relatively successful in creating justice, especially in directing students to get schools based on their residence. The challenge occurred in the student's educational process. Principals and teachers lack understanding of the equity spirit that underlies the implementation of the school zoning system and gives equal treatment to all students. As a result, students with less prior academic ability will be left behind those with good or excellent prior academic skills. Further research that can be explored from the results of this study is to explore how the impact of the zoning system in other regions may have different results from the Surakarta and Yogyakarta regencies.